2021
DOI: 10.1080/23311975.2021.1963167
|View full text |Cite
|
Sign up to set email alerts
|

The effect of consumer ethnocentrism on the acceptance of imported grocery products in Harare, Zimbabwe

Abstract: The study investigated the effect of consumer ethnocentrism on the acceptance of imported grocery products in Harare, Zimbabwe. Using a cross-sectional survey of 505 consumers, independent-samples T-test, analysis of variance and structural equation modelling were used to test research hypotheses. Results show that gender, age and education significantly influence consumer ethnocentrism. Income was found to have an insignificant influence on consumer ethnocentrism. Results also show that consumer ethnocentrism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Some disease categories such as antenatal and postpartum, gastro-intestinal problems, malaria, reproductive problems, respiratory problems and sexually transmitted infections are among the ten major causes of death in Zimbabwe (Nyabani 2021). Research by Muchandiona (2013) showed that gastro-intestinal disorders and respiratory infections reported in several local councils in Zimbabwe are a result of poor solid waste management which has worsened in the country over the last three decades. Similarly, gastro-intestinal disorders, such as dysentery and diarrhoea are also a major concern in neighbouring countries such as Mozambique (Ribeiro et al 2010, Bruschi et al 2011, Barbosa et al 2020 and South Africa , Maroyi 2016, Rankoana 2022).…”
Section: Use Categories With High Numbers Of Use Reportsmentioning
confidence: 99%
“…Some disease categories such as antenatal and postpartum, gastro-intestinal problems, malaria, reproductive problems, respiratory problems and sexually transmitted infections are among the ten major causes of death in Zimbabwe (Nyabani 2021). Research by Muchandiona (2013) showed that gastro-intestinal disorders and respiratory infections reported in several local councils in Zimbabwe are a result of poor solid waste management which has worsened in the country over the last three decades. Similarly, gastro-intestinal disorders, such as dysentery and diarrhoea are also a major concern in neighbouring countries such as Mozambique (Ribeiro et al 2010, Bruschi et al 2011, Barbosa et al 2020 and South Africa , Maroyi 2016, Rankoana 2022).…”
Section: Use Categories With High Numbers Of Use Reportsmentioning
confidence: 99%